Traktat dobrosąsiedzki z 1991 r. a niemieckie dziedzictwo kulturowe w Polsce - Zybura, Marek (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
Controversies surrounding the German cultural heritage in Poland after World War II were one of the most important fields of conflict in Polish–German relations in this period. The attitude to this issue in Poland has been changing during the whole postwar period, but the act decisive in neutralizing the confrontational atmosphere surrounding this topic was the Treaty of Good Neighbourship and Friendly Cooperation signed in 1991
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne